Is this blended-learning, or another thing? - Belchior-Rocha, H. (2021)
Today there are many forms of online use to support training, education and information dissemination. There's been a lot of confusion about the concept of online learning and we may not be able to get a definitive definition of it but hopefully, we can clarify concepts and the objective of this presentation is to be able to have a satisfying definition to understand the way our institution uses online content for our undergraduate students. Online learning in higher education is often pointed out as a good alternative, in the planning and organization of teaching/learning activities. Although there is resistance to its adherence by older or traditionalist teachers, because they do not master the tools and pedagogical innovation with digital technologies and also some resistance to the format, as it seconds the role of the teacher, shifting the axis of learning towards the student. Our University uses currently a platform for online learning, where there are small online courses that are additinally for some of the mandatory or optative curricular courses for the first year of the Undergraduate Programme. The structure of the online courses is normally of videos in varying number, followed by quizzes to assess the knowledge retained by the viewer of the video. It requires a minimum percentage of result to proceed to the next video. This model for training and education gives both the student and the teacher the opportunity of enrichment if, on the one hand, the student creates some autonomy, on the other hand, does not lose contact with teacher presence.